The Development of Digital Content in the Form of Photo Alblum for Publicizing Secondary City Tourism Attractions on the Online Platform of Backbone Mcot Page - Thamwipat, Kuntida; Princhankol, Pornpapatsorn; Aeowjaroen, Pannaphon; Preedakullaphat, Phakjirapron; Suwanmanee, Kanyawee (Siam Communication Review, 2023)
The purposes of this research were 1) to the develop and determine the quality of digital content in the form of photo alblum for publicizing secondary city tourism attractions on the online platform Backbone Mcot page. 2)To assess the sample perception and 3) To assess satisfaction towards the developed digital content based on the ADDIE Model. .Collected data from a sample of 30 followers on the Backbone MCOT online platform using a purposive sampling from people who watched digital content in the form of photo album for publicizing secondary city tourism attractions on the Backbone MCOT online platform who are willing to answer the questionnaire. The results of development was digital content in the form of photo alblum 5 sets .The results of content quality assessment was at a very good level ( = 4.60, S.D.= 0.45). Media quality assessment results was at a very good level ( = 4.85, S.D.= 0.30). The sample perception was at the highest level ( = 4.78, S.D. = 0.49) and the sample satisfaction was at the highest level ( = 4.85, S.D. = 0.35), respectively. it could be concluded that the developed digital content in the form of photo alblum for publicizing secondary city tourism attractions on the online platform Backbone Mcot page developed with good quality can be used for public relations.